Mid-term Result of Total Knee Arthroplasty in the Young Osteoarthritis Patients - Kawinwonggowit, MD, Viroj; Wongsak, MD, Siwadol; Padungpak, MD, Prachya (Journal of Southeast Asian Orthopaedics, 2022)
Background: The primary goals of total knee arthroplasty (TKA) are to relieve pain and improve function in inflammatory and degenerative knee arthritis. Long-term clinical success has been shown in elderly patients. Objective: The purpose of this study was to evaluate the clinical and radiographic results of TKA in patients with advanced stage osteoarthritis of the knee joints where the patients were younger than fifty-five years of age at the time of operation. Materials and methods: The authors retrospectively reviewed the results of 70 patients with osteoarthritis who were 55 years or younger (mean age, 52.2 years) and who had received a fixed-bearing cemented TKA prosthesis and patellar resurfacing. The patients were assessed with regard to clinical, radiographic and knee motion assessment. Kaplan-Meier analysis of implant survival was performed. Results: The mean preoperative and postoperative knee motion was 97.0° and 119.8°, respectively (P < 0.01). At the latest follow-up, Knee Society knee clinical scores improved from 45.6 to 83.3 points (P < 0.01) and Knee Society knee functional scores improved from 45.9 to 72.6 points (P < 0.01). There were three revision TKA that included aseptic loosening for two knees and septic loosening for one knee. The mean follow-up was 8.7 years (range, 5.0-16.0). The Kaplan-Meier survivorship analysis of implants showed that the rate of survival was 97.9% (95% CI, 90 to 99) at 10 years postoperatively and 96.9% (95% CI, 80 to 98) at 15 years postoperatively when revision was defined as the end point. Discussion: The study showed improvement of functional and clinical knee scores at mid-term follow-up in patients with advanced stage osteoarthritis of the knee where the patients were younger than fifty-five years of age. However, there is concern in the findings of previous literature regarding the success of TKA in young patients. It will be important to determine the functional outcome and ability to return to an active lifestyle in younger patients. Long-term follow-ups in the second decade should be performed because younger patients will likely live long enough to require revision surgery.